Beef traders' and consumers' perceptions on the development of a natural pasture-fed beef brand by smallholder cattle producers in South Africa. Issue 3 (12th October 2016) - Marandure, Tawanda; Mapiye, Cletos; Makombe, Godswill; Nengovhela, Baldwin; Strydom, Phillip; Muchenje, Voster; Dzama, Kennedy
Abstract : Beef traders' and consumers' perceptions on the development of a natural pasture-fed beef (NPB) brand by smallholder cattle producers were investigated. In total, 18 meat traders (five abattoirs and 13 beef retailers) and 155 beef consumers were interviewed using structured questionnaires. All meat traders had the potential but were not willing to support the development of a NPB brand citing smallholder farmers' limited ability to supply sufficient volumes of high-quality cattle. Consumers (81%) were prepared to purchase NPB upon availability on the market but were not willing (80%) to pay a brand premium. Logistic regression model results showed that consumers' willingness to buy NPB and pay a premium were influenced ( P < 0.05) by gender, household size, income source, meat preference, meat consumption frequency, money spent on beef, frequency of beef purchases and consumption. Overall, beef traders and consumers held positive impressions regarding the development of a NPB brand by smallholder cattle producers but were not willing to support its development. Positive impressions held by value chain partners on the development of a NPB brand provide a basis for advancing development of a NPB brand. Initial efforts should enhance farmers' capacity to supply sufficient volumes of high-quality cattle.